The low-fidelity DNA Pol IV accelerates evolution of pathogenicity genes in Pseudomonas aeruginosa - Sofía D. Castell; Consuelo M. Fernandez; Ignacio N. Tumas; Lucía M. Margara; María C. Miserendino; Danilo G. Ceschin; Roberto J. Pezza; Mariela R. Monti (Communications Biology)
Abstract Specialized DNA polymerases facilitate various cellular processes. Despite extensive research, the mutagenic effects of these error-prone enzymes on genomes are not fully understood. Here we show that Pol IV promotes genomic instability in Pseudomonas aeruginosa by misincorporating oxidized guanine nucleotides. This activity led to a distinctive mutational signature, characterized by A-to-C transversions occurring preferentially at AT sites flanked by a 5’G and/or 3’C. Furthermore, Pol IV preferentially targeted pathogenicity genes located at specific chromosomal locations near the replication termination region and rRNA-encoding operons. Half of the mutation events catalyzed by Pol IV impaired gene function. This can be attributed to the bias of Pol IV for mutating codons with its preferred sequence contexts, leading to substitutions to unreactive alanine and glycine residues. Remarkably, mutation signatures identified for Pol IV were found in clinical isolate genomes of P. aeruginosa, providing compelling evidence for its role in genetic diversification during pathogen adaptation.